(3CUhd bGfhf GdeQGaYGJ GdeOfjI hGdJLGQjI (B:s (3OQGSI aj GdJfXje GdbVGFj hGdENJUGU, OYhi GdNUheI, GdMce h GdWYf ajg (B/s - (3gfOj, CMeOs ((3GdEScfOQjI(B: s (3OGQ GdLGeYI GdLOjOjI(B, s, 2002)
(3GdfXGe GdbVGFj(B:(3JQJjH h JTcjd GdeMGce,GdbGVj(B-(3GdGNJUGU,GdGNJUGU GdhXjaj Ch GdhdGFj,GdGNJUGU GdfhYj h Gdbjej(B-(3GdGNJUGU GdbjejGdGNJUGU GdeMdj(B-(3GdOYhi,TQhW bHhd GdOYhi,JbSje GdOYGhj, GSYeGd GdOYhi(B-(3GdNUheI,GLQGAGJ QaY GdOYhi,GYdGf ChQGb GdeQGaYGJ,ehGYjOGdeQGaYGJ,YhGQV GdNUheI,GdLRGAGdGLQGFj(B-(3GdMce h GdWYf,GdMceGdbVGFj,GdWYf (B.s
Keywords: (3GdbVGAs; (3GdeMGces